Obamacare wars : federalism, state politics, and the Affordable Care Act - Béland, Daniel; Rocco, Philip; Waddan, Alex, 1964- (Studies in government and public policy., 2016)
This book on federalism and health insurance reform explores the politics of implementing the 2010 Affordable Care Act in the 50 states.